Brewery waste derived activated carbon for high performance electrochemical capacitors and lithium-ion capacitors. (1st April 2023) - Magar, Sandesh Darlami; Leibing, Christian; Gόmez-Urbano, Juan Luis; Cid, Rosalía; Carriazo, Daniel; Balducci, Andrea
Abstract: In this study we report about the synthesis and characterization of an activated carbon (AC) displaying very large surface area ( ∼ 3600 m 2 g −1 ) obtained from a cheap and abundant brewery waste product (Brewer's spent grains, BSG). AC based electrodes prepared from BSG demonstrated a very high specific capacitance (46 F g −1 ) and capacitance retention when evaluated in symmetric Electrical Double Layer Capacitors (EDLCs) devices with organic electrolytes. We showed that these electrodes can be successfully utilized for the realization of lab scale EDLCs and Lithium-ion Capacitors exhibiting very high energy and power densities as well excellent cycling stability (85% capacitance retention after 200 h of float test). Considering these results, the BSG-derived AC can be certainly considered as very promising material, which can contribute to the development of high performance, cost effective and eco-friendly high-power devices.